International Conference on Design and Test of Integrated Systems in Nanoscale Technology, 2006. DTIS 2006. 2006
DOI: 10.1109/dtis.2006.1708651
|View full text |Cite
|
Sign up to set email alerts
|

Supply voltage glitches effects on CMOS circuits

Abstract: Among the attacks applied on secure circuits, fault injection techniques consist in the use of a combination of environmental conditions that induce computational errors in the chip that can leak protected informations. The purpose of our study is to build an accurate model able to describe the behaviour of CMOS circuits in presence of deliberated short supply voltage variations. This behaviour depends strongly on the basic gates (combinational logic, registers.. .) that make up the circuit. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…One level down from that is the paper by Djellid-Ouar, Cathebras and Bancel [4] which concluded that D-flip-flops This work was not supported and do not represent the approval or rights of any third parties. 1.…”
Section: A Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…One level down from that is the paper by Djellid-Ouar, Cathebras and Bancel [4] which concluded that D-flip-flops This work was not supported and do not represent the approval or rights of any third parties. 1.…”
Section: A Backgroundmentioning
confidence: 99%
“…A faster clock will increase the chance of a successful fault (due to timing violations). In practice, we cannot over-clock much past the default rate of 37MHz or we will run into non-voltage glitch related timing violations that prevent the circuit from working properly 4 . However, in our case, because of the noisy design of our glitching setup, we picked f = 12 MHz since it was the fastest we were able to go without running into a variety of signal integrity issues.…”
Section: B Parametersmentioning
confidence: 99%
“…This dependency can be misused to force faulty behavior during the chip's operation. Short supply voltage variations, introduced by glitches on the supply voltage line, can produce computational errors in CMOS circuits [9]. Examples of such errors are memory bit flips, corrupted instructions, and jumping over instructions in a microprocessor.…”
Section: Background -Voltage Fault Injectionmentioning
confidence: 99%
“…A simpler approach to inject faults into the system is voltage FI, where the supply voltage is over-or undervolted for a short moment [9]. The technique is also referred to as voltage glitching.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few papers have been dedicated to a deep investigation of the underlying fault injection mechanism. The most significant paper [9] studied accurately the effects of a voltage glitch on the DFFs of a CMOS circuit. It showed, on a simulation basis, that power supply glitches cannot induce faults into DFFs.…”
Section: B Power Glitch Induced Faultsmentioning
confidence: 99%